Analysis of marketing strategies, campaigns and projects of IDLC Finance Limited - Abedin, Saiyara Arsheen (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.